KEGIATAN KONFERENSI KASUS DALAM PENYELESAIAN MASALAH PESERTA DIDIK DI SMA N 11 PADANG - Putri, Des Tiara (Bimbingan dan Konseling, 2014)
This research is motivated by an example that is the case that researchers have found in schoolwhen PPLBK school, a student conduct violation took place during school hours. The focus of thisresearch is a case conference deploy activities starting from planning, implementation, evaluationand follow-up to overcome the problems of students in SMAN 11 Padang. This research wasconducted with a qualitative descriptive approach. The informants were: 3 BK teacher, viceprincipal, homeroom parents and learners. The instrument used in this study were interviews anddocumentation, data were subjected to triangulate and hold membercheck, as well as thetechniques used in the processing of data through data reduction, data presentation and conclusion.Based on the results of the effectiveness of case conferences in solving student in SMAN 11Padang, the result of planning, implementation, evaluation and follow-up were conducted BKteachers have not done systematically.